2023
DOI: 10.3390/molecules28155657
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High-Pressure Homogenization on Enhancing the Extractability of Phytochemicals from Agri-Food Residues

Abstract: The primary objective of the Sustainable Development Goals is to reduce food waste by employing various strategies, including the reuse of agri-food residues that are abundantly available and the complete use of their valuable compounds. This study explores the application of high-pressure homogenization (HPH), an innovative nonthermal and green treatment, for the recovery of bioactive compounds from agri-food residues. The results demonstrate that the optimized HPH treatment offers advantages over conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…This finding aligns with previous results, which demonstrated that under processing conditions comparable to those utilized in this study, HPH treatment (80 MPa, 10 passes) reduced particle sizes of tomato pomace to a range of 55-90 µm, while HSM treatment resulted in a broader size range of 580-1020 µm. Furthermore, the variation in particle size induced by HPH pre-treatment also enhanced suspension stability [29].…”
Section: Effect Of Hph-assisted Extraction On the Recovery Yield Of C...mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding aligns with previous results, which demonstrated that under processing conditions comparable to those utilized in this study, HPH treatment (80 MPa, 10 passes) reduced particle sizes of tomato pomace to a range of 55-90 µm, while HSM treatment resulted in a broader size range of 580-1020 µm. Furthermore, the variation in particle size induced by HPH pre-treatment also enhanced suspension stability [29].…”
Section: Effect Of Hph-assisted Extraction On the Recovery Yield Of C...mentioning
confidence: 99%
“…The highest cutin content observed in HPH-treated samples confirmed the contribution of HPH to improving the cutin isolation process by depolymerizing cutin in an alkaline solution. This improvement is attributed to HPH's ability to micronize plant tissue in suspension [24,29], creating favorable conditions for subsequent chemical hydrolysis and enhancing extraction efficiency, even at low NaOH concentrations.…”
Section: Effect Of Hph-assisted Extraction On the Recovery Yield Of C...mentioning
confidence: 99%
“…Consequentially, new policies and efforts toward the design of appropriate management of AFRs have to be put in place to contribute to a sustainable development, respectful of the social and environmental facets [2]. Within this frame, the exploitation of AFRs presents new opportunities to extract and purify high value-added compounds [3][4][5],…”
Section: Introductionmentioning
confidence: 99%